Successful pregnancy and delivery in a rare case of pemphigus vulgaris - Marging, Yapi; Sharma, Nalini; Verma, Shikha; S. Singh, Ahanthem (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Pemphigus vulgaris (PV) is a rare autoimmune bullous dermatosis characterized by flaccid blisters and extensive erosions on the skin and mucous membranes. While in the active stage of PV lesions, it is reported to be linked to infertility, and its presence during pregnancy is exceedingly rare. Pregnancies complicated by pemphigus vulgaris often result in adverse obstetrical outcomes, including prematurity, neonatal skin lesions, and even fetal demise. Our patient, a chronic pemphigus vulgaris case, was being treated with rituximab, a pregnancy category C drug. Later upon conceiving, her medication was switched to oral steroids, which were later changed to intravenous steroids due to a flare-up in the third trimester. Her elective lower segment caesarean section was done with delivery of a female baby weighing 2.6 kg with APGAR scores of 8 and 9 at one minute and five minutes respectively, without any apparent skin lesions. During the postpartum period, her skin lesions resolved completely by the time of her routine postnatal follow-up.